2023
DOI: 10.1038/s41598-023-28678-x
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphonium conjugated gold nanotriangles impact Pi3K/AKT pathway in breast cancer cells: a photodynamic therapy approach

Abstract: Although gold nanoparticles based photodynamic therapy (PDT) were reported to improve efficacy and specificity, the impact of surface charge in targeting cancer is still a challenge. Herein, we report gold nanotriangles (AuNTs) tuned with anionic and cationic surface charge conjugating triphenylphosphonium (TPP) targeting breast cancer cells with 5-aminoleuvinic acid (5-ALA) based PDT, in vitro. Optimized surface charge of AuNTs with and without TPP kill breast cancer cells. By combining, 5-ALA and PDT, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Remarkably, the half‐maximum inhibitory concentration (IC 50) of SWCNTs was determined to be 1.07 μg/mL after 24 h. Although the mechanism behind the solid antiproliferative activity of SWCNTs against breast cancer cells is not entirely understood, this effect has been seen. According to studies, bioactive compounds may be responsible for imparting anticancer capabilities to SWCNTs 24,25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the half‐maximum inhibitory concentration (IC 50) of SWCNTs was determined to be 1.07 μg/mL after 24 h. Although the mechanism behind the solid antiproliferative activity of SWCNTs against breast cancer cells is not entirely understood, this effect has been seen. According to studies, bioactive compounds may be responsible for imparting anticancer capabilities to SWCNTs 24,25 …”
Section: Resultsmentioning
confidence: 99%
“…According to studies, bioactive compounds may be responsible for imparting anticancer capabilities to SWCNTs. 24,25…”
Section: Fabrication Of Functionalized Swcnts and Their Anticancer Ac...mentioning
confidence: 99%
“…The created gold nanoconjugate system, according to the author, is an effective anti-cancer medication that targets mitochondria and causes cellular apoptosis in breast cancer. 145…”
Section: Utilizing Conjugated Polymers Copolymers and Nanocomposites ...mentioning
confidence: 99%
“…The created gold nanoconjugate system, according to the author, is an effective anti-cancer medication that targets mitochondria and causes cellular apoptosis in breast cancer. 145 A unique triarylamine (TPA)-modified hemithioindigo (HTI)-based aggregation-induced emission (AIE) photosensitizer, 6Br-HTI-TPA-OMe, was successfully developed by Wang et al, who found that reversible control over 1 O 2 generation was possible due to the covalent link between the triarylamine AIE photosensitizing moiety and the HTI switch unit. The nanoparticles (NPs) synthesized from amphiphilic phospholipids also displayed photochromic activity in water.…”
Section: Utilizing Conjugated Polymers Copolymers and Nanocomposites ...mentioning
confidence: 99%